Fungal Exposure and Low Levels of IL-10 in Patients with Sarcoidosis - Terčelj, Marjeta; Stopinšek, Sanja; Ihan, Alojz; Salobir, Barbara; Simčič, Saša; Rylander, Ragnar (Pulmonary Medicine, 2014)
Background and Objectives. Sarcoidosis is an inflammatory disease with increased levels of inflammatory cytokines. Previous studies have shown a relation between the degree of granuloma infiltration and serum cytokine levels, except for interleukin- (IL-) 10. The aim of the study was to further investigate the serum levels of IL-10 in patients with sarcoidosis and relate them to fungal exposure in terms of the amount of fungi in the air of their homes and β-glucan in bronchoalveolar lavage (BAL) fluid. Methods. Patients with sarcoidosis (n=71) and healthy controls (n=27) were enrolled. IL-10 was determined in serum. BAL was performed and the amount of β-glucan was measured. Domestic exposure to fungi was determined by measuring airborne β-N-acetylhexosaminidase (NAHA) in the bedrooms. Results. At high levels of fungal exposure (domestic fungal exposure and β-glucan in BAL), serum IL-10 values were lower than at low and intermediate exposure levels. Conclusion. The low serum IL-10 values at high fungal exposure suggest that fungal cell wall agents play a role in granuloma formation in sarcoidosis by inhibiting the secretion of the anti-inflammatory cytokine IL-10.